2014
DOI: 10.1007/s11367-014-0791-5
|View full text |Cite
|
Sign up to set email alerts
|

Environmental evaluation and comparison of selected industrial scale biomethane production facilities across Europe

Abstract: Purpose The two main reasons for producing biomethane as renewable fuel are reduction of climate impacts and depletion of fossil resources. Biomethane is expected to be sustainable, but how sustainable is it actually? This article contributes to the clarification. Therefore, the environmental impacts of several biomethane facilities all over Europe were assessed. A special focus is put on the differences between the facilities as they follow different production routes. Methods The method used for evaluation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…LCAs available in the literature provide a variety of insights on WtE systems that combine anaerobic digestion with energy recovery, or biogas value chains. In general, biogas energy systems have lower greenhouse gas (GHG) emissions than fossil energy systems, especially when biogas is used as fuel in transportation (Liu et al 2013, Niu et al 2013, Lozanovski et al 2014, Lyng et al 2015. The results are sensitive to the management of the digestate; open storage leads to uncontrolled emissions of GHG like CH4 and nitrous oxide (N2O) (Blengini et al 2011, De Meester et al 2012, Boulamanti et al 2013) and the use of digestate in agriculture increases the risk for human toxicity, acidification and eutrophication potentials due to the heavy metals (Patterson et al 2011) and the high nutrient level it contains (Lozanovski et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LCAs available in the literature provide a variety of insights on WtE systems that combine anaerobic digestion with energy recovery, or biogas value chains. In general, biogas energy systems have lower greenhouse gas (GHG) emissions than fossil energy systems, especially when biogas is used as fuel in transportation (Liu et al 2013, Niu et al 2013, Lozanovski et al 2014, Lyng et al 2015. The results are sensitive to the management of the digestate; open storage leads to uncontrolled emissions of GHG like CH4 and nitrous oxide (N2O) (Blengini et al 2011, De Meester et al 2012, Boulamanti et al 2013) and the use of digestate in agriculture increases the risk for human toxicity, acidification and eutrophication potentials due to the heavy metals (Patterson et al 2011) and the high nutrient level it contains (Lozanovski et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In general, biogas energy systems have lower greenhouse gas (GHG) emissions than fossil energy systems, especially when biogas is used as fuel in transportation (Liu et al 2013, Niu et al 2013, Lozanovski et al 2014, Lyng et al 2015. The results are sensitive to the management of the digestate; open storage leads to uncontrolled emissions of GHG like CH4 and nitrous oxide (N2O) (Blengini et al 2011, De Meester et al 2012, Boulamanti et al 2013) and the use of digestate in agriculture increases the risk for human toxicity, acidification and eutrophication potentials due to the heavy metals (Patterson et al 2011) and the high nutrient level it contains (Lozanovski et al 2014). A recent study of Iordan et al (2016) highlights the sensitivity of biogas systems to the choice of climate metrics and the influence of the near-term climate forcers (NOx, SOx, particulate matters, black carbon and organic carbon).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the residue after digestion is rich in nutrients and can be used as a fertiliser in crop production [ 2 ]. In a number of studies, production of biogas has been shown to offer significant advantages over other forms of bioenergy production and it has been rated one of the most energy-efficient and environmentally beneficial technologies for bioenergy production [ 3 , 4 ]. Biogas can be produced from many different types of materials, including various types of waste streams from the food and feed industry, sludge from wastewater treatment plants, plant residues and manure from agriculture and energy crops [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to direct combustion on-site, upgrading biomethane and using it as a vehicle fuel seems to be environmentally advantageous [73]. Not surprisingly, biomethane from organic waste and sewage sludge also is rated superior compared to fossil fuels [74][75][76]. However, there are some critical factors like feedstock type, fugitive methane emissions, digestate management, and fossil fuel comparators which can negatively affect the environmental performance of biomethane [76][77][78].…”
Section: Discussionmentioning
confidence: 99%